Family communication management from Muslim adolescent perspective / Aziyah Abu Bakar - Abu Bakar, Aziyah (2015)
Communication management is very important in Islam, especially in the family. Family communication pattern often causing family conflict, especially on young Muslims. The purpose of this study is to analyze what kind of strategies use by adolescents and their parents in family communication, whether they choose to use avoidance strategy, cooperation strategy or dominance strategy.This study consists a survey involving 360 respondents of urban Muslim adolescents on the East Coast of Peninsular Malaysia.The stratified and systematic sampling was used as a method of selecting a sample.Data were analyzed with a focus on descriptive statistics such as frequency, percentage, average and standard deviation and Pearson correlation analysis.The findings indicated that strategy of avoiding, cooperation strategy and dominance strategy has a positive and significant correlation with oriented conversation and the orientation of conformity.The study also found that most of adolescent Muslims use cooperation strategy and strategy of avoiding compared to the strategy of dominating during the conflict with the parents.Thus family harmony can be maintained.